Effects of single and combined exposure to BDE-47 and PFOA on distribution, bioaccumulation, and toxicity in blue mussel (Mytilus galloprovincialis) - Qianqian Geng (Elsevier, 2021)
The contamination of 2,2’,4,4’-Tetrabrmodiphenyl ether (BDE-47) and perfluorooctanoic acid (PFOA) has drawn a worldwide attention over the risks in ecological and food safety. In this work, blue mussel (Mytilus galloprpvincialis) was employed to investigate the combined effects of BDE-47 (10 ng mL-1) and PFOA (100 ng mL-1) on tissue distribution, accumulation, elimination, and toxicity. Results suggested that BDE-47 and PFOA accumulated mostly in digestive gland, followed by gills and gonad, and M. galloprovincialis displayed higher accumulation capacity to BDE-47 than PFOA. Co-exposure treatment reduced the accumulation of BDE-47, and enhanced the accumulation of PFOA. Furthermore, biochemical and histopathological tests revealed that the aggravated toxicity in co-exposure groups was mainly attributed to the oxidative stress and damage of tissue structure. This work could be helpful to get a better understanding of the combined behaviors and cumulative risks of BDE-47 and PFOA in marine ecosystem.